Bathymetry of the Amundsen Sea Embayment sector of West Antarctica from Operation IceBridge gravity and other data. Issue 3 (4th February 2017) - Millan, Romain; Rignot, Eric; Bernier, Vincent; Morlighem, Mathieu; Dutrieux, Pierre
Abstract: We employ airborne gravity data from NASA's Operation IceBridge collected in 2009–2014 to infer the bathymetry of sub–ice shelf cavities in front of Pine Island, Thwaites, Smith, and Kohler glaciers, West Antarctica. We use a three‐dimensional inversion constrained by multibeam echo sounding data offshore and bed topography from a mass conservation reconstruction on land. The seamless bed elevation data refine details of the Pine Island sub–ice shelf cavity, a slightly thinner cavity beneath Thwaites, and previously unknown deep (>1200 m) channels beneath the Crosson and Dotson ice shelves that shallow (500 m and 750 m, respectively) near the ice shelf fronts. These sub–ice shelf channels define the natural pathways for warm, circumpolar deep water to reach the glacier grounding lines, melt the ice shelves from below, and constrain the pattern of past and future glacial retreat. Key Points: Deep troughs (700 m) beneath major ice shelves in the Amundsen Sea sector of Antarctica reveal pathways for warm waters to melt glaciers Bed mapping extends in a seamless fashion from multibeam offshore to high‐resolution reconstruction inland for the first time The data should be an important asset for ice sheet and ocean modelers and improve our understanding of this sector